Zanesljivost ocenjevanja hranjenja in požiranja s slovenskim prevodom standardiziranega testa - Marot, Valerija (Rehabilitacija (Ljubljana), 2017)
Introduction: Feeding and swallowing disorders are relatively frequent in early childhood, especially in children with various neurological impairments. Effective and safe feeding in the early childhood directly affects the growth and development of children. Reliable clinical assessment of feeding and swallowing represents a starting point for the effective management and therapeutic treatment of children. The study aimed to evaluate whether the direct assessment in vivo is as reliable as video-recorded assessment of feeding with Dysphagia Disorder Survey (DDS). Methods: With the DDS test we evaluated feeding and swallowing of children with neurological impairment. Children were video-recorded during feeding or eating a usual meal. The first speech pathologist assessed children eating in vivo, while the recording was being prepared. The second speech pathologist assessed those recordings later. In order to demonstrate the agreement between in-vivo and video-recorded evaluation, we calculated the intra-class correlation coefficient. Results: We evaluated 19 children with developmental neurological impairment aged from three to 12 years. Statistical analysis revealed a high intra-class correlation coefficient of the total DDS score (ICC 0,98), as well as for the majority of DDS items (ICC between 0,68 and 0,69). Conclusions: The assessment of eating with DDS in vivo and based on video- recordings is highly reliable. Based on that we believe that the DDS could also be used without previous video-recording of eating.
Keywords: Child; DDS; Dysphagia Disorder Survey; eating disorders; Feeding and Eating Disorders; motnje hranjenja; neurological impairment; nevrološke okvare; otrok; reliability; test DDS; zanesljivost ocenjevanja